Supporting Requirements Elicitation Practices - Mohd Ilias Bin M Shuhud; Alexander Richter; Aishah Ahmad (Springer, 2024)
In this paper, we examine the practices in requirements elicitation activities from the perspective of a developer of software projects. By doing so, we want to contribute to a better understanding of how the main activities between stakeholders can be supported by IT, particularly social software. We have interviewed six key persons from five different software projects and identified the potential roles of social software to improve in five main activities of requirements elicitation. We present these critical points in the context of the cases and discuss them across the cases.